Lexington and Concord : the battle heard round the world - Daughan, George C. (W.W. Norton & Company, 2018)
Reinterprets the battle that launched the American Revolution, arguing that the war was based as much in economic concerns as political ones and that most militiamen volunteered on behalf of their livelihoods and in protest of serf-like living conditions.